A Study on Synthesis of Chemical Crosslinked Polyvinyl Alcohol-Based Alkaline Membrane for the Use in Low-Temperature Alkaline Direct Ethanol Fuel Cell - Gupta U.K.; Pramanik H. (My University, 2025)
In this paper, an economical and simple procedure was adopted for the fabrication of chemically crosslinked polyvinyl alcohol (PVA)-based KOH-doped alkaline membrane for the use in an alkaline direct ethanol fuel cell (ADEFC). The membrane parameters, namely, water uptake, KOH uptake, and ionic conductivity were systematically evaluated. The ionic conductivity of the synthesized membrane was in the order of 9 × 10-3 S/cm. The performance of the synthesized alkaline membrane is evaluated in a single ADEFC. Commercial Pt-Ru (30 wt %: 15 wt %)/C and Pt (40 wt %)/high surface area carbon (CHSA) from Alfa Aesar, Haverhill, MA, were used for anode and cathode, respectively. The performance of the membrane was further evaluated in a single cell using different grades of membranes containing different glutaraldehyde (GA) concentration, anode and cathode electrocatalyst loading, ethanol concentration, and KOH concentration. The maximum open circuit voltage (OCV) of 0.73 V was obtained at a temperature of 35 °C for anode feed containing 2 M ethanol and 1 M KOH for the membrane crosslinked with 2.5 wt % glutaraldehyde doped with 6 M KOH. The maximum power density of 4.15 mW/cm2 at a current density of 20.69 mA/cm2 was obtained for the same condition. The optimum electrocatalyst loading was 1 mg/cm2 of Pt-Ru/C at the anode and 1 mg/cm2 of Pt/CHSA at the cathode. The performance of KOH-doped chemically crosslinked PVA membrane was comparable with the published literature. © 2019 by ASME.